Zinc Critical Levels and Supplying Powers of Takhli, Loei, and Khorat Soil Series for Corn Production - Amnat Suwanarit; Chiranee Vanichkul; Preeda Parkpian (Agriculture and Natural Resources, 1992)
Pot experiments were conducted to examine critical levels and supplying powers of Zn in Takhli, Loei and Khorat soil series, as well as reliabilities of two methods of soil analysis, namely, extraction with 0.1N HCl and extraction with DTPA (pH 7.3). Results showed that Takhli soil was so severely deficient in Zn that Zn visual deficiency symptoms were observed whereas Loei soil was Zn-deficient but not so severely that visual deficiency symptoms could be observed. Khorat soil series was estimated to be able to support corn production for at least 37 years before it needed Zn application for maximum growth. Narrowest ranges of extracted Zn that covered critical levels for Takhli, Loei and Khorat soil series were 2.5-4.8, 9.6-13.9 and 6.9-16.0 ppm, respectively when extracted with 0.1 N HCl and were 1.2-2.0, 8.6-12.6 and 3.4-12.4 ppm, respectively when extracted with DTPA. Considering the three soils as one group, the narrowest ranges were 4.8-9.6 and 2.0-8.6 ppm for extractions with 0.1 N HCl and with DTPA, respectively. Narrowest ranges of Zn concentrations in corn plants were 18-32, 50-57 and 52-107 ppm for Takhli, Loei, and Khorat soil series, respectively. Considering the three soils as one group, the narrowest range of Zn in plants was 32-52 ppm. It was concluded that extraction with 0.1 N HCl gave slightly more reliable prediction than extraction with DTPA. However, differences in critical levels found for the individual soils suggested that Zn concentration in plants would provide more reliable prediction than amounts of Zn extracted from soils by the two methods. Takhli and Loei soil series needed 6.3 and 43.8 kg Zn/ha to produce maximum growth of corn plants. However, 62.5 kg Zn/ha applied to the three soils was not toxic to corn.